Analisis Kinerja Pengadaan Barang dan Jasa Pemerintah dengan Pendekatan Balanced Scorecard - Sinta Dewi Parida; Shalma Putri Rigianti; Vera Vebrianty; Sigit Djalu Purwoko (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine the performance of government procurement of goods and services using the Balanced Scorecard approach. By using the literature or literature study method, a technique for collecting data is by conducting a review study of books, literature, notes and reports that are related to this problem. Based on the research results, it shows that in general, the procurement performance can be considered quite good. Several aspects have been assessed positively. Financial performance shows a high level of budget realization and efficient use of resources. From a customer perspective, the level of customer satisfaction is also quite good, reaching 85%. Meanwhile, from an internal business process perspective, the efficiency of procurement of goods and services reached 95%. From a growth and learning perspective, efforts to improve performance have produced positive results.